Repetitive transcranial magnetic stimulation ameliorates chronic pain behavior and modulates the brain transcriptome in a mouse model of chronic constriction injury - Tianying Li; Guanwen Lin; Tao Zhang; Yani Guo; Yongjin He; Jing Luan; Jin Wang; Dan Lyu; Yiqi Weng; Xin Jin (Brain Research Bulletin)
Background and aim: Neuropathic pain (NP), caused by nerve injury or dysfunction, poses a significant clinical challenge due to its limited response to conventional pharmacological treatments. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising non-invasive neuromodulatory approach for NP management. This study aimed to evaluate the therapeutic efficacy of rTMS in alleviating NP induced by chronic constriction injury (CCI) in a mouse model and to investigate the underlying molecular mechanisms through transcriptomic profiling. Procedures: Adult male mice underwent CCI surgery to induce NP and were randomly assigned to receive either rTMS (5 Hz or 10 Hz) or sham stimulation. rTMS was applied once daily for 14 consecutive days, beginning on postoperative day 7. Behavioral assessments—including paw withdrawal latency (PWL) and paw withdrawal threshold (PWT)—were conducted to evaluate thermal hyperalgesia and mechanical allodynia, respectively. Anxiety-like behaviors were assessed using the open field test (OFT) and elevated plus maze (EPM). At the end of the treatment period, brain tissues were harvested for RNA sequencing and differentially expressed genes (DEGs) were identified and analyzed. Results and conclusion: rTMS at both 5 Hz and 10 Hz significantly improved PWL and PWT in CCI mice and reduced anxiety-like behaviors. Transcriptomic analysis revealed that CCI induced dysregulation of 66 genes, while rTMS partially normalized gene expression patterns. Functional enrichment analysis indicated significant involvement of pathways related to inflammatory responses, transporter activity, and ion channel regulation. These findings support the potential of rTMS as a multifaceted, non-invasive therapeutic strategy for neuropathic pain, with molecular mechanisms likely involving modulation of neuroinflammatory and neuroexcitatory pathways.